Correction: Theoretical design of stable hydride clusters: isoelectronic transformation in the EnAl4−nH7+n− series. Issue 31 (30th March 2017) - Giraldo, Carolina; Ferraro, Franklin; Hadad, C. Z.; Ruiz, Lina; Tiznado, William; Osorio, Edison
Abstract : Correction for 'Theoretical design of stable hydride clusters: isoelectronic transformation in the E n Al4− n H7+ n − series' by Carolina Giraldo et al., RSC Adv., 2017, 7, 16069–16077.